By Mouse & Frog - Freedman, Deborah (Deborah Jane), 1960- (Viking, an imprint of Penguin Group (USA), 2015)
"Mouse has one idea about what a book should be and how to tell a story. Frog has another. What happens when these two very different friends try to create a book together?"--